2021
DOI: 10.1186/s12884-020-03420-x
|View full text |Cite
|
Sign up to set email alerts
|

Uterotonics for prevention of postpartum haemorrhage: EN-BIRTH multi-country validation study

Abstract: Background Postpartum haemorrhage (PPH) is a leading cause of preventable maternal mortality worldwide. The World Health Organization (WHO) recommends uterotonic administration for every woman after birth to prevent PPH. There are no standardised data collected in large-scale measurement platforms. The Every Newborn Birth Indicators Research Tracking in Hospitals (EN-BIRTH) is an observational study to assess the validity of measurement of maternal and newborn indicators, and this paper reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These findings highlight an urgent requirement for improved evidence to support an expanded typology of respectful care that intentionally includes newborns [19], and highlights the importance of disaggregating data by mode of birth. This was a recurrent theme across the EN-BIRTH study [49][50][51][52].…”
Section: Discussionmentioning
confidence: 92%
“…These findings highlight an urgent requirement for improved evidence to support an expanded typology of respectful care that intentionally includes newborns [19], and highlights the importance of disaggregating data by mode of birth. This was a recurrent theme across the EN-BIRTH study [49][50][51][52].…”
Section: Discussionmentioning
confidence: 92%
“…The qualitative data analysis presented in this paper identified common barriers and enablers for labour ward register recording across all indicators, using health worker and data collector responses together. Indicatorspecific mixed-methods linked analyses will be presented in other linked papers to further explore subthemes and differences between cadres [57][58][59][60][61][62]. It was beyond the scope of this study for the EN-BIRTH data collectors to directly observe or measure the detailed process of register filling (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Quality of care had many gaps compared to global standards, notably regarding timing of care. For example, although provision of uterotonics to prevent postpartum hemorrhage was universally high across all five hospitals, the observational data showed that overall only 16% of women received uterotonics within 1 min after birth [18]. Regarding neonatal resuscitation, most non-breathing newborns were observed to receive bag-mask-ventilation, but overall only 1% within the recommended 1 min after birth [21].…”
Section: Registers Performed Particularly Well For Indicatorsmentioning
confidence: 98%
“…This supplement starts with three papers on measurement systems covering: EN-BIRTH electronic data collection [15], survey-report for validity of 33 indicators [16], and barriers/enablers to recording in routine registers [17]. Subsequent papers detail findings for the following maternal and newborn coverage indicators: uterotonics to prevent postpartum haemorrhage [18], immediate newborn care including breastfeeding practices [19], chlorhexidine for umbilical cord care [20], neonatal resuscitation [21], KMC [22], neonatal infection antibiotic management [23]. Two papers assess validity and data quality for the outcomes of birthweight [24] and stillbirth [25].…”
Section: What Is New and What Have We Learned?mentioning
confidence: 99%
See 1 more Smart Citation